Media Busy Book Untuk Menstimulasi Kemampuan Spasial Anak usia 5-6 Tahun Di Gugus V Kecamatan Buleleng - Ni Putu Jyoti Kamala; Putu Aditya Antara; Made Vina Arie Paramita (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
This development research is motivated by the use of media and learning models in kindergarten, which still need to be optimal, and the lack of learning media used to apply learning. The research aims to develop busy book media to stimulate the spatial abilities of children aged 5-6 years. This development research uses the Research and Development (R&D) method with the ADDIE model. The subjects of this research were 2 experts, namely media experts, learning content experts, and 3 school teachers. The object of this research is busy book media in spatial learning. The data collection method used was a questionnaire. The instrument used to collect data is the rating scale sheet. The research results show that the average score for suitability by media experts is 4.34, and suitability for learning content experts is 4.56, with both classifications being very good. The average practicality score by teachers is 4.29. The form of development of this research is a learning media, namely busy book media, which is used to improve the spatial abilities of children aged 5-6 years. It is concluded that teachers can use this busy book media to stimulate spatial abilities in children. It has been tested for validity and practicality with very good classification, so this busy book media is appropriate and suitable for use.